Agrobiodiversity of cactus pear (Opuntia, Cactaceae) in the Meridional Highlands Plateau of Mexico - Reyes-Aguero, Juan Antonio; Aguirre Rivera, Juan Rogelio (JNRD - Journal of Natural Resources and Development, 2011)
Mexico is characterized by a remarkable richness of Opuntia, mostly at the Meridional Highlands Plateau; it is also here where the greatest richness of Opuntia variants occurs. Most of these variants have been maintained in homegardens; however, the gathering process which originated these homegardens has been disrupted over the past decades, as a result of social change and the destruction of large wild nopaleras. If the variants still surviving in homegardens are lost, these will be hard to recover, that is, the millenary cultural heritage from the human groups that populated the Mexican Meridional Highland Plateau will be lost forever. This situation motivated the preparation of a catalogue that records the diversity of wild and cultivated Opuntia variants living in the meridional Highlands Plateau. To this end, 379 samples were obtained in 29 localities, between 1998 and 2003. The information was processed through Twinspan. All specimens were identified and preserved in herbaria. Botanical keys and descriptions were elaborated. The catalogue includes information on 126 variants comprising 18 species. There were species with only one variant (Opuntia atropes, O. cochinera, O. jaliscana, O. leucotricha, O. rzedowskii and O. velutina), two (O. durangensis, O. lindheimeri, O. phaeacantha and O. robusta), five (O. joconostle and O. lasiacantha), seven (O. chavena), 12 (O. hyptiacantha and O. streptacantha), 15 (O. ficus-indica), 22 (O. albicarpa), and up to 34 (O. megacantha). Additionally, 267 common cactus pear names were related to those variants.
Keywords: Agrobiodiversity; Ex situ; In situ; Opuntia streptacantha; Opuntia ficus-indica